Zatrudnienie za pośrednictwem platformy internetowej jako przejaw „uberyzacji” pracy - Bakalarz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The sharing economy has left a strong mark on the modern labour market. One of the popular forms of earning in the sharing economy is crowd employment. In the present paper the author analyzes a tripartite relationship between the crowdsourcer, crowdsourcing platforms and a crowdworker. The author is looking for legal models describing the particular relationships. He is considering whether the nature of employment can be attributed to them. The paper is of a reporting nature. The legal assessment refers to Polish law.
Keywords: Uberization; new forms of employment; labour law; sharing economy